Two new species of the Empis subgenus Lissempis (Diptera: Empididae) from the Caucasus - Shamshev, Igor; Kustov, Semen (Zootaxa, 2013)
Two new species of the genus Empis subgenus Lissempis Bezzi, 1909 are described from the Caucasus: Empis (Lissempis) azishtauensis sp. nov. (Russia: Adygea, Krasnodar Territory) and E. (L.) krasnodarensis sp. nov. (Russia: Krasnodar Ter-ritory). An updated key to European species of the subgenus is given.